THE DEPRESSION SYMPTOMS IN THE PIECES OF A WOMAN BY KORNEL MUNDRUCZO (2020) - Siti Nurindah; Anita Sari (LPPM Universitas PGRI Jombang, 2026)
The study aims to identify and analyze the symptoms of depression reflected in the main character and how the main character copes with her depression in the film Pieces of a Woman. This study employs a descriptive qualitative method and uses Beck and Alford's (2009) theory of depression as the primary framework. The findings show that Martha exhibits several key symptoms of depression, such as emotional, cognitive, motivational, vegetative, and physical manifestations. Furthermore, the study reveals how Martha copes with her depression through a progression of strategies such as Cognitive Therapy and Cognitive Behavioral Therapy. The significance of these findings lies in providing a deeper psychological understanding of how depression is represented in film, particularly in portraying grief-related depression. This study contributes to literary and film analysis by demonstrating the relevance of psychological theories in interpreting character development and mental health issues, as well as offering insight into coping mechanisms that may raise awareness of depression and its treatment in real-life contexts